2022
DOI: 10.1136/bmjopen-2020-046410
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of NIHR research training: perceptions of the programmes: a qualitative interview study

Abstract: ObjectivesThe UK National Institute for Health Research (NIHR) training programmes were created to build and sustain research capacity in healthcare. Following the training programme 10-year strategic review, this qualitative study aimed to deepen understanding of facilitators and barriers for those progressing through NIHR-supported research careers.DesignSemistructured qualitative study.Data collection and analysisTelephone interviews conducted between May and August 2017 were digitally recorded, transcribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…One aspect of this challenge around clinical academic progression related to anxiety about future funding. This concern has previously been identified at earlier points on the clinical academic career pathway, with ‘difficulty obtaining research grants’ considered the main barrier to award success for ACFs 24 27. CLs perceive increasingly higher levels of competition for clinical academic roles acting as a barrier to progression and the Medical Schools’ Council clinical academic workforce survey has shown that between 2006 and 2021 there was an 84% increase in CLs employed by universities but a reduction of 5% in senior clinical academic positions, which does, in part, support this view 28.…”
Section: Discussionmentioning
confidence: 86%
“…One aspect of this challenge around clinical academic progression related to anxiety about future funding. This concern has previously been identified at earlier points on the clinical academic career pathway, with ‘difficulty obtaining research grants’ considered the main barrier to award success for ACFs 24 27. CLs perceive increasingly higher levels of competition for clinical academic roles acting as a barrier to progression and the Medical Schools’ Council clinical academic workforce survey has shown that between 2006 and 2021 there was an 84% increase in CLs employed by universities but a reduction of 5% in senior clinical academic positions, which does, in part, support this view 28.…”
Section: Discussionmentioning
confidence: 86%
“…These results are timely as a report last year by the House of Lords Science and Technology Committee has declared that the clinical research environment in the NHS is on a dangerous precipice. 2 , 3 , 4 A crisis has been declared especially at the clinical lecturer / postdoctoral level, with a leaky pipeline of clinical academics resulting in dwindling numbers and diminishing gains from translational research. 2 Multifactorial reasons are given for this, with difficulty finding any longer-term academic positions and reduced total renumeration that disincentivises clinical academia cited as important factors.…”
Section: Discussionmentioning
confidence: 99%
“…The most reported barriers had issues to do with lack of protected time, lack of research skills/knowledge/experience, lack of support, workload/work pressures, lack of funds, sustainable research pathways, sta ng, nature of working (parttime/in exible), not being fully prepared for research from college and personal factors [43,45,[50][51][52]]. These factors were also highlighted in studies conducted in other developed countries [39,40,48,[53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%